The Event and Its Pasts: 20th-Century Argentina and the Extreme Violence of the 1970s - Franco, Marina; Pontoriero, Esteban (Hispania Nova, 2026)
This article explores the characteristics of state repression in twentieth-century Argentina, through its continuities and changes, with the aim of in serting the State terrorism of the seventies into a deeper historical weft. On the basis of an exhaus tive bibliographic survey, added to the results of our own research, different keys to analytical reflection are studied, through a series of temporalities, in the long, medium and short term. In the different sections, the historical processes of construction of the “internal enemy”, the violent responses of the State, the mechanisms of exception and the growing power of the Armed Forces in internal politics, in articulation with their role in repression, are addressed. The article aims to make a contribution to the development of future proposals and lines of research on the history of repression and extreme violence in Argentina.